How Does Public Information on Central Bank Intervention Strategies Affect Exchange Rate Volatility? - Mundaca, B. Gabriela (2012)
Intervention operations in the foreign exchange market are used by the Banco Central de Reserva del Peru to manage both the level and volatility of their exchange rates. The Banco Central de Reserva del Peru provides information to the market about the specific hours of the day interventions would take place and the total amount of intervention. It consistently buys and sells on the foreign exchange market to avoid large appreciations and depreciations of the Peruvian nuevo sol against the U.S. dollar (Sol/USD), respectively. The estimates in this paper indicate that past information on interventions has moved the sol in the intended direction but only during the time the Banco Central de Reserva del Peru has announced it would be active in the foreign exchange market. The authors also find that the expectation of future interventions by the Banco Central de Reserva del Peru decreases the volatility of the sol when it intervenes to avoid an appreciation of the sol; however, the opposite occurs when the intervention takes place to defend the sol from depreciation. Indeed, the sol has been less volatile during periods when the Banco Central de Reserva del Peru has intervened than otherwise.